Effects of irradiance during growth on tolerance of geranium to sub- and supra-optimal boron supply - S. Mishra; S. A. Heckathorn; J. M. Frantz; C. Krause (Biologia Plantarum, 2014)
In our previous study on geranium, we showed that increases in growth irradiance from sub-optimal to near-optimal could delay boron deficiency effects on photosynthesis. In this study, we further investigated the effects of growth irradiance on tolerance to B stress by growing geranium (Pelargonium × hortorum cv. Maverick White) under sub- to supra-optimal B concentrations (4.5, 45, and 450 μM) and under three irradiances of 100, 300, or 500 μmol m-2 s-1 PAR for 30 d. In general, at low and medium irradiances, sub- and supra-optimal B availability decreased root and shoot dry masses, but at high irradiance, the B stress was prevented. Net photosynthetic rate decreased by the supra-optimal B concentration at the high irradiance only suggesting B-related photoinhibition. Tissue B content and root specific B uptake only modestly decreased by the low B treatment, but increased greatly by the high B availability, and the higher irradiance decreased the tissue B content and the root B uptake only at the low and medium B supplies. Interestingly, the increases in irradiance decreased the content and uptake of all other nutrients, except Fe uptake. Effects of the B stress on the content of other nutrients were variable, but the B stress often exacerbated decreases in nutrient content with the increasing irradiance which would be especially important under nutrient-limiting conditions. Hence, in this study, the B stress effects on growth were mitigated by the increases in growth irradiance, which offset negative effects on physiology, and the protective effects of irradiance were likely caused by its positive effects on plant carbon/energy status rather than on tissue B content or B uptake.